Peningkatan Literasi Keuangan UMKM melalui Pelatihan Harga Pokok Produksi dan Laporan Laba Rugi di Desa Panembong Garut - Hamdah, Dida Farida Latipatul; Anggraeni, Windi Ariesti; Ningsih, Winda; Fadilah, Resmi Afifah (Ikatan Cendekiawan Muda Akuntansi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving regional economic growth, including in Panembong Village, Garut Regency, which is known as a center for hijab and knitting production. However, MSME actors in this area still face challenges in accurately calculating the Cost of Goods Sold (COGS) and preparing profit and loss statements. These difficulties have a direct impact on setting rational selling prices and ensuring business sustainability. As a solution, the community service team from Garut University organized intensive training for 30 MSME participants using a participatory approach, including focus group discussions (FGD), material presentations, case studies, and technical mentoring. The training materials covered understanding the concept of COGS, cost classification, preparation of basic profit and loss statements, and hands-on practice using worksheets. The results showed a significant improvement in participants’ understanding of cost concepts and the relationship between COGS and selling price. This activity not only provided knowledge but also enhanced the confidence of MSME owners in making financial decisions. This training served as an important strategy to improve financial literacy and strengthen the competitiveness of MSMEs in the Garut Regency.